Nanoimaging and Nanospectroscopy of Polaritons with Time Resolved s‐SNOM. Issue 5 (9th September 2019) - Yao, Ziheng; Xu, Suheng; Hu, Debo; Chen, Xinzhong; Dai, Qing; Liu, Mengkun
Abstract: The development of electronics and photonics is entering a new era of ultrahigh speed sensing, data processing, and telecommunication. The carrier frequencies of the next‐generation electronic devices inevitably extend beyond radio frequencies, marching toward the nominally photonics‐dominated territories, e.g., terahertz and beyond. As a result, electronic and photonic techniques naturally merge and seek common ground. At the forefront of this technical trend is the field of polaritonics, where polaritons are half‐light, half‐matter quasiparticles that carry the properties of both "bare" photons and "bare" dipole‐carrying excitations. The Janus‐faced nature of polaritons renders the unique capability of operando control using photoexcitation or applied electric field. Here, state‐of‐the‐art ultrafast polaritonic phenomena probed by scattering‐type scanning near‐field optical microscope ( s ‐SNOM) techniques is reviewed. The ultrafast dynamical control and loss‐reduction of the polariton propagation are discussed with special emphasis on the creation and probing of the tip or edge induced plasmon– and phonon–polaritons in low‐dimensional systems. The detailed technical aspects of s ‐SNOM and its possible future development are also presented. Abstract : A review on the principle and recent progress in the field of real‐space imaging and spectroscopy of various types of polaritons using scattering‐type scanning near‐field optical microscopy ( s ‐SNOM) are provided here, with a special focus on time‐resolved experiments. New directions for the s ‐SNOM and polaritonic research, especially the study of polaritonic dynamics at nanoscale are also presented.